Tipificação da negação do Holocausto como crime no direito penal brasileiro - Baker, Milena Gordon (2019)
The following thesis sets out an analysis of Holocaust denial from the perspective of intolerance and hate speech, specifically in the field of criminal law. As such, this study has been developed with the aim of investigating the legal approaches that should be adopted towards Holocaust denial in order to appropriately respond to the issues that it presents. Further, through analysis of international and Brazilian criminal law, this thesis seeks to answer the question of whether Holocaust denial in Brazil should be treated as a distinct type of crime as a method of implementing constitutional guarantees much like in the case of the repudiation of racism and active efforts combatting hate speech